A SYSTEMATIC APPROACH TO THE STUDY OF FAMILY VALUES IN THE MODERN RUSSIAN SOCIETY - Irina P. Lotova (Статистика и экономика, 2016)
The author in detail analyzes the main research paradigms in contemporary Russian sociology of the family ("progressive", "crisis").In the article essentially, substantial characteristic and classification of family values. In particular, the classification of value orientations of the family by the criterion of civilizational affiliation (traditional, modern and post-modern).The essence of the transformation of family values in modern Russian society.